Public real estate as a driver for urban regeneration: an overview of municipal urban plans in Italy - Alessio Floris (City, Territory and Architecture)
Abstract After a long season aimed at regulating urban growth, the theoretical debate and the operational practice of urban planning are now focused on transforming existing cities. In this context, public real estate, particularly buildings and areas that no longer fulfill their original purpose or for which the land use is no longer suitable, has emerged as a crucial resource for cities due to its heterogeneity and widespread availability. In Italy, however, the emphasis has been on selling public assets to address financial deficits, rather than meeting local needs or public interests. This paper focuses on the relationship between public real estate and urban planning strategies at the local level, through the analysis of the municipal urban plans of a selection of urban centers across the Italian territory, to assess how unused or decommissioned public real estate assets are addressed within the planning processes, with a view to urban regeneration.